Increase of TREM2 during Aging of an Alzheimer’s Disease Mouse Model Is Paralleled by Microglial Activation and Amyloidosis - Brendel, Matthias; Kleinberger, Gernot; Probst, Federico; Jaworska, Anna; Overhoff, Felix; Blume, Tanja; Albert, Nathalie L.; Carlsen, Janette; Lindner, Simon; Gildehaus, Franz Josef; Ozmen, Laurence; Suárez-Calvet, Marc; et al. (Frontiers in Aging Neuroscience, 2017)
Heterozygous missense mutations in the triggering receptor expressed on myeloid cells 2 (TREM2) have been reported to significantly increase the risk to develop Alzheimer’s disease (AD). Since TREM2 is specifically expressed by microglia in the brain, we hypothesized that soluble TREM2 (sTREM2) levels may increase together with in vivo biomarkers of microglial activity and amyloidosis in an AD mouse model as assessed by small animal positron-emission-tomography (µPET). In this cross-sectional study, we examined a strong amyloid mouse model (PS2APP) of four age groups by µPET with [18F]-GE180 (glial activation) and [18F]-florbetaben (amyloidosis), followed by measurement of sTREM2 levels and amyloid levels in the brain. Pathology affected brain regions were compared between tracers (dice similarity coefficients) and pseudo-longitudinally. µPET results of both tracers were correlated with terminal TREM2 levels. The brain sTREM2 levels strongly increased with age of PS2APP mice (5 vs. 16 months: +211%, p < 0.001), and correlated highly with µPET signals of microglial activity (R = 0.89, p < 0.001) and amyloidosis (R = 0.92, p < 0.001). Dual µPET enabled regional mapping of glial activation and amyloidosis in the mouse brain, which progressed concerted leading to a high overlap in aged PS2APP mice (dice similarity 67%). Together, these results substantiate the use of in vivo µPET measurements in conjunction with post mortem sTREM2 in future anti-inflammatory treatment trials. Taken human data into account sTREM2 may increases during active amyloid deposition.